MENGUKUR EFEKTIVITAS GOOGLE KELAS DARI PERSEPSI SISWA SMP ISLAM AL-ISRA MENGGUNAKAN USE QUESTIONNAIRE - Maulida, Rusyda; Puspitasari, Tita; Bani, Bani (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
The Covid-19 pandemic has rapidly changed the world of education due to the obligation to utilize technology. However, technology still cannot replace the role of teachers and learning interactions between students and teachers because learning is about acquiring knowledge and values, cooperation, and competence. This pandemic situation challenges each individual’s creativity in using technology to develop the world of education. Google Kelas is one of the free and popular tools to bridge the gap between students and teachers. Google Kelas is a widely used tool during the Covid-19 pandemic because schools or teachers are not required to pay to take advantage of its features. This research was conducted to determine the effectiveness of using Google Kelas. The research was conducted through a quantitative research design. The research sample using this semi-structured survey consists of 87 students who have used Google Kelas for at least one semester in their class. The survey was given using the USE Questionnaire method and was calculated using a Likert scale. Based on the assessment of the use of Google Kelas at SMP Al-Isra, the following results were obtained: the value on the usefulness aspect was 85.2, which indicates that Google Kelas has outstanding usability, which means that Google Kelas can be received very well; the value on the aspect of satisfaction is 83.2 which indicates that Google Kelas provides excellent satisfaction which means that Google Kelas can meet the needs of respondents; the score on the ease of use aspect is 83.6 which indicates that Google Kelas is very friendly to use which means that Google Kelas can be used very well by respondents, and the score on the ease of learning aspect is 86.4 which shows that Google Kelas has perfect easy learning which means that Google Kelas can be learned very well.